POLA KOMUNIKASI TOKOH AGAMA ISLAM DI DESA WISATA KEBANGSAAN WONOREJO-SITUBONDO UNTUK MENJAGA TOLERANSI MUSLIM-NON MUSLIM - Imam Mashuri (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2022)
The communication pattern of Islamic religious leaders in Wonorejo Village in order to maintain Muslim and non-Muslim tolerance has been going well. This is inseparable from the long history of the establishment of Wonorejo Village and the efforts of religious leaders in building tolerance from an early age. The type of research conducted is descriptive qualitative research. By collecting data through observations, interviews, and documents. For data analysis using data reduction, data display and data confirmation. For the validity of the data using the triangulation method. The data taken in the form of primary and secondary data. The pattern of communication carried out includes social and religious aspects. The social aspect is carried out by praying together during village meetings and village clean-up events. Religious aspects are carried out during Christmas by carrying out friendships with Christian residents, Reciting the Maulid of the Prophet Muhammad SAW by inviting other religious leaders, providing halal food during celebrations by non-Muslims by slaughtering animals by Islamic religious leaders, arranging burial locations for Muslims. non-Muslims in one burial location. Providing consulting services for married couples who are constrained by different religions, Providing counseling and guidance to Muslim citizens to live tolerantly with minority residents in order to anticipate the entry of radicalism in Wonorejo Village.